Conformal Stretch Sensors for High Resolution Motion Sensing and Control. Issue 4 (17th January 2019) - Lin, Lancy; Chu, Michael; Park, Sun‐Jun; Zakashansky, Julia Alice; Khine, Michelle
Abstract: While motion sensors such as accelerometers are commonplace now, highly sensitive conformal sensors that can quantify fine motion with high resolution remain to be realized. Current strain sensors exhibit a trade‐off between dynamic range and strain sensitivity; these sensors therefore are not suitable for applications that require both large strain and excellent signal resolution, such as gesture control for virtual and augmented reality or feedback or prosthetics. Shape‐memory polymers coupled with thin films on stretchable elastomeric support substrates have recently emerged as fabrication platforms that improve strain sensor characteristics. Herein, skin‐mountable strain sensors are introduced, with large dynamic ranges (over 350%), higher gauge factor (GF) with linear responses to strain (from 0–150%), smaller footprint sizes, and less hysteresis compared to other sensors. It is demonstrated that these sensors are able to resolve down to 5° resolution of the proximal interphalangeal joint, which would enable gesture control for gaming and other motion sensing and control applications. Because these sensors have a small form factor and are low‐cost and disposable, such technology can find various electronic applications. Abstract : Highly stretchable and sensitive strain sensors are fabricated using shape memory polymers. These sensors exhibit low electrical hysteresis and a small form factor for high resolution needs. Finger joint angle measurements with 5° resolution demonstrate their applicability to monitor subtle human motions.